Comparison of pre-operative and post-operative liver function tests in patients undergoing laparoscopic cholecystectomy at different intra-peritoneal pressures - Akhter, Zahida; Nabi, Naveed; Kakroo, Showkat M.; Mehraj, Sharik (International Journal of Research in Medical Sciences, 2023)
Background: Establishing pneumoperitoneum is a pre-requisite for any laparoscopic procedure. However, its adverse effects are not uncommon. Increased intra-peritoneal pressure during laparoscopic cholecystectomy is expected to alter the liver function test (LFT) in immediate post-operative period, which may raise concerns in surgeons’ mind regarding integrity of biliary tract. The aim of our study was to compare the post-operative LFT with pre-operative values in patients undergoing laparoscopic cholecystectomy at different pneumoperitoneal pressures and to assess its clinical significance. Methods: It was a prospective observational study in which the enrolled patients were divided into 2 groups. Group 1 patients underwent laparoscopic cholecystectomy at 12 mm Hg pressure and group 2 underwent the surgery at 15 mmHg pressure. Pre-operative LFT was compared with post-operative LFT done 24 hours and 2 weeks after surgery. Results: Among 73 included patients, 41 constituted group 1 and 32 were included in group 2. Statistically significant difference was observed in hepatic transaminases between pre-operative and post-operative (1st POD) values. Mean AST in group 1: 34.7 versus 51.4 U/l; in group 2, the values were 35.1 versus 50.9 U/l respectively. Mean ALT in group 1: 36.3 versus 50.1 U/l; in group 2, values were 32.9 versus 45.6 U/l respectively. However, the enzymes normalized in all patients in 2 weeks without any adverse clinical outcome. Conclusions: Early post-operative transient elevation of hepatic transaminases after laparoscopic cholecystectomy is not associated with any adverse clinical outcome.